Back to nature: new urban policy and environmental governance in Canada's capital. Issue 12 (1st December 2016) - Picton, Roger M.
ABSTRACT: Drawing on a growing literature on the integration of environmental discourses into urban development schemes, this paper charts the urban development of LeBreton Flats, in Ottawa, Ontario, Canada. An industrial neighbourhood expropriated as part of a post-war urban renewal project, LeBreton Flats is being redeveloped in line with green, mixed-use urban planning principles. The paper investigates how national narratives are intertwined within urban development practices and argues that historically and geographically embedded expressions of national nature first used to justify post-war expropriation are being adapted as part of urban neo-liberal naturalised practices of central-city redevelopment.